RARE VASCULAR DISEASES OF THE FEMALE REPRODUCTIVE TRACT: A LITERATURE REVIEW ON THE ETIOLOGY, DIAGNOSIS, AND TREATMENT OF UTERINE ARTERIOVENOUS MALFORMATIONS AND VULVAR ANEURYSMS - Justyna Rajczyk; Tomasz Rajczyk; Marcel Bobiński; Aleksandra Sosińska; Zuzanna Wieczorek; Adam Szymczak; Monika Wiczuk-Wiczewska; Justyna Bartol; Wiktoria Skowron; Kamil Kania (International Journal of Innovative Technologies in Social Science, 2026)
Vascular disorders of the female reproductive tract, including uterine arteriovenous malformations (AVMs) and aneurysms or pseudoaneurysms of the uterine and pudendal arteries, represent extremely rare but potentially life-threatening conditions in gynecology. Due to their low incidence and nonspecific clinical presentation, these entities pose significant diagnostic and therapeutic challenges. Although uncommon, they may result in severe hemorrhage, particularly in the postpartum period or following intrauterine procedures.The aim of this narrative review is to summarize current evidence regarding the etiology, clinical manifestations, diagnostic imaging modalities, and treatment strategies for rare vascular abnormalities of the female reproductive system. A literature search was conducted using PubMed, Scopus, and Web of Science databases, including articles published between 2000 and 2025.Available data indicate that color Doppler ultrasonography is the primary diagnostic tool, while magnetic resonance imaging and angiography play a crucial role in confirmation and treatment planning. Selective endovascular embolization has emerged as the gold-standard therapy, providing high efficacy in hemorrhage control while preserving uterine integrity and reproductive potential in most patients. Despite favorable outcomes, standardized diagnostic and therapeutic algorithms are lacking. Further multicenter studies and case registries are required to optimize management strategies for these rare but clinically significant conditions.